Surface modification of biodegradable polymer - Chian, Hwey Ying. (2009)
Biodegradable polymer creates great interest for tissue engineering application for its biocompatibility. Nature of polymer however sets restrictions on direct usage due to hydrophobic surface profile. Surface modification is carried out to increase hydrophilicity of PCL and PLC film to enchance biocompatibility with human cells. This final year project reports on the surface modification via wet chemical reaction on PCL and PLC surfaces. For polymers with no polar functional groups, surface modification is highly dependent on the degree of aminolysis performed to introduce amino groups onto the polymer surface. Aminolysis process induce pores on the polymer surface to enhance attachment of amino group. Higher degree of aminolysis however may induce mechanical change to the polymer, decreasing the effectiveness of surface modification. 7 time points are carried out for aminolysis. Ninhydrin and SEM characterization confirms the degree of aminolysis and optimizes the condition for surface modification. Results from Ninhydrin showed highest intensity at 2min for PCL and 5min for PLC and gradual decrease in intensity for other time points. SEM images showed high concentration of pores at the optimal time point and extensive corrosion on the polymer surface at a longer time point. L929 fibroblast cell culture determines the viability and biocompatibility of non-surface modified, gelatin molecules immobilized and gelatin gel immobilized polymer films. 7 days cell surface interaction studies were done to non-modified and surface modified PCL and PLC. Biocompatibility results were positive, validating the viability of using biodegradable polymer. hMSC human cells were cultured on polymer surface and subjected to mechanical stimuli and characterized for any upregulation of gene.